1989
DOI: 10.1111/j.1530-0277.1989.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Nonverbal Right Hemisphere Processing by Chronic Alcoholics

Abstract: The theory that chronic alcoholism produces a right hemisphere deficit has generally been tested using visuospatial tasks. The present report tested the theory using three tasks that tap functions, other than visuospatial abilities, which have been failed by patients with right hemisphere damage. The first task assesses the ability to draw a correct inference by integrating information from two unrelated sentences. The second taps the patient's capacity to appreciate humor. The third requires the patient to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
4
18
0
Order By: Relevance
“…These include: greater impairments on performance (nonverbal) tasks than on verbal tasks of IQ tests (Parsons and Leber 1981); reduced visual-spatial and perceptual-motor performance (Bowden and McCarter 1993;Ellis and Oscar-Berman 1989;Parsons 1987); emotional abnormalities (Clark et al 2007b;Oscar-Berman et al 1990); atypical laterality patterns on dichotic listening tests (Drake et al 1990), but only for the male alcoholics); impaired performance for nonverbal stimuli on visual search tasks (Bertera and Parsons 1978); and limited attentional resources (Evert and Oscar-Berman 2001;Smith and Oscar-Berman 1992). It is important to note, however, that while many studies have found evidence to support the "right hemisphere hypothesis" of alcoholism-related cognitive decline, others have not found such support (Cermak et al 1989;Mungas et al 1994).…”
Section: Hypothalamusmentioning
confidence: 91%
“…These include: greater impairments on performance (nonverbal) tasks than on verbal tasks of IQ tests (Parsons and Leber 1981); reduced visual-spatial and perceptual-motor performance (Bowden and McCarter 1993;Ellis and Oscar-Berman 1989;Parsons 1987); emotional abnormalities (Clark et al 2007b;Oscar-Berman et al 1990); atypical laterality patterns on dichotic listening tests (Drake et al 1990), but only for the male alcoholics); impaired performance for nonverbal stimuli on visual search tasks (Bertera and Parsons 1978); and limited attentional resources (Evert and Oscar-Berman 2001;Smith and Oscar-Berman 1992). It is important to note, however, that while many studies have found evidence to support the "right hemisphere hypothesis" of alcoholism-related cognitive decline, others have not found such support (Cermak et al 1989;Mungas et al 1994).…”
Section: Hypothalamusmentioning
confidence: 91%
“…AD patients exhibit impairments in functions associated with activation of the PFC e.g. increased impulsivity and risky decision making [26], [27], impaired emotional facial perception [28][30], emotional prosody perception [31] and humour processing [32], [33]. There is also growing evidence for similarities in decision making between substance abusers and VMPC lesion patients, indicating that these patients share an underlying emotional dysfunction (for review, see [34]).…”
Section: Introductionmentioning
confidence: 99%
“…Cermak et al (1989) employed verbal and nonverbal tasks to test right brain damaged patients, alcoholic subjects, and normal elderly controls. Alcoholics performed better than patients with brain damage but worse than elderly controls on two dimensions: (1) making correct inferences by integrating information and (2) humor appreciation.…”
mentioning
confidence: 99%